THE CORRELATION BETWEEN STUDENTS HABIT IN READING ENGLISH AND VOCABULARY ACHIEVEMENT IN SMA UNISMUH MAKASSAR - Husnaini; Bahrun Amin; Maharida (Journal of Language Testing and Assessment, 2021)
This study aims to determine the correlation between students' reading habits in English and vocabulary achievement at the second grade (IPA) of SMA Unismuh Makassar. In this study, using the correlation description method, which consists of two instruments in collecting data, namely questionnaires and tests. This research was conducted in a class at SMA Unismuh Makassar where the sample chosen by the researcher was class two science consisting of 27 students in one class. The results in this study indicate that variable X to variable Y has a correlation with the degree of the correlation, namely a weak correlation in the form of a negative correlation. The negative correlation is the higher the variable X, the lower the Y variable and vice versa. The data analysis calculation of r is the lower r-table (-0.287 <0.3809). This means that there is no significant correlation between students' reading habits in English and vocabulary achievement. In other words, hypothesis H0 is accepted and hypothesis H1 is rejected.